Синдром Петрушки: [роман] / Дина Рубина - Рубина Дина Ильинична (Эксмо, 2012)
Экземпляры: ф. 1 (20140314) / Инвентарный номер: 100856 / Цена: 125.00 / Авт.знак: Р 82 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6